Citrus Consumption and Risk of Cutaneous Malignant Melanoma - Wu, Shaowei (J Clin Oncol, 2015)
PURPOSE: Citrus products are widely consumed foods that are rich in psoralens and furocoumarins, a group of naturally occurring chemicals with potential photocarcinogenic properties. We prospectively evaluated the risk of cutaneous malignant melanoma associated with citrus consumption. METHODS: A total of 63,810 women in the Nurses' Health Study (1984 to 2010) and 41,622 men in the Health Professionals Follow-Up Study (1986 to 2010) were included. Dietary information was repeatedly assessed every 2 to 4 years during follow-up. Incident melanoma cases were identified through self-report and confirmed by pathologic records. RESULTS: Over 24 to 26 years of follow-up, we documented 1,840 incident melanomas. After adjustment for other risk factors, the pooled multivariable hazard ratios for melanoma were 1.00 for overall citrus consumption < twice per week (reference), 1.10 (95% CI, 0.94 to 1.30) for two to four times per week, 1.26 (95% CI, 1.08 to 1.47) for five to six times per week, 1.27 (95% CI, 1.09 to 1.49) for once to 1.5 times per day, and 1.36 (95% CI, 1.14 to 1.63) for ≥ 1.6 times per day (P(trend) < .001). Among individual citrus products, grapefruit showed the most apparent association with risk of melanoma, which was independent of other lifestyle and dietary factors. The pooled multivariable hazard ratio for melanoma comparing the extreme consumption categories of grapefruit (≥ three times per week v never) was 1.41 (95% CI, 1.10 to 1.82; P(trend) < .001). CONCLUSION: Citrus consumption was associated with an increased risk of malignant melanoma in two cohorts of women and men. Nevertheless, further investigation is needed to confirm our findings and explore related health implications.